Viabilidade para a geração de energia elétrica a partir do biogás proveniente da suinocultura em Medianeira - PR - Victoria, Geovana Grigio (2023)
Brazilian pig farming has greatly intensified in the last 20 years, as it is an activity of recognized economic importance. On the other hand, the increase in the concentration of animals has brought some challenges that directly impact the environment, due to the high level of pollution from the large volume of waste generated by pig farming, which has a high load of pollutants. However, with sustainable production models, it is possible to reduce such impacts and increase profits from this activity, through the generation of biogas from pig farming waste and its conversion into electrical energy. The state of Paraná is a larger producer of pigs, with Medianeira housing large agro industries, for this reason it is important to analyze the energy potential of pig farming in the municipality and the benefits that the distributed generation of electricity from biogas can bring to the producers of this activity. The objective of this study was to determine the economic viability of four scenarios: 1. Installation of biodigesters and generator engines on small, medium, and large swine properties, producing energy and compensating directly to the producer, 2. Sale of electrical energy produced on the properties, 3. Installation of a biodigester and sale of biogas from producers, 4. Construction of a thermoelectric plant in the municipality of Medianeira-PR, using waste from the city’s entire plant to compensate for electrical energy in public buildings. To analyze these four scenarios and determine whether the projects are economically viable, the Biogás Invest platform provided by CIBiogás was used to carry out the simulations. The results obtained showed that on small properties (250 sows or 900 finishing pigs) it is not viable to proceed with the project in any of the scenarios in which the system is installed on pig farming properties. In cases of medium-sized properties (600 sows or 2000 animals in finishing) and large ones (1000 sows or 4000 animals in finishing) it is feasible to install the system both to compensate and for the sale of electricity or the sale of biogas. In the case of using waste from the entire Medianeira pig herd, which has a herd of 131,000 animals, to produce electrical energy in a single plant, the result showed that it can generate large revenues and obtain payback in 2 years of operation. of the substation.